Piranhas - Grossman, Susan M. (New York : Dillon Press ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1994)
Describes the physical characteristics, habitat, and life cycle of piranhas, and explains that their scary reputation may be exaggerated.
Includes index.
Keywords: Piranhas; Piranhas